Rapid Detection of SARS-CoV-2 Based on the LAMP Assay Associated with the CRISPRCas12a System - Karoline Almeida Felix de Sousa; Carolina Kymie Vasques Nonaka; Ricardo Khouri; Clarissa Araújo Gurgel Rocha; Carlos Gustavo Regis-Silva; Bruno Solano de Freitas Souza (Diagnostics, 2023)
Background: The global public health system has been severely tested by the COVID-19 pandemic. Mass testing was essential in controlling the transmission of the SARS-CoV-2; however, its implementation has encountered challenges, particularly in low-income countries. The urgent need for rapid and accurate tests for SARS-CoV-2 has proven to be extremely important. Point-of-care tests using the CRISPR system for COVID-19 have shown promise, with a reported high sensitivity and rapid detection. The performance of a CRISPR-based SARS-CoV-2 testing system was reported in this study. Methods: A total of 29 nasopharyngeal samples were evaluated, including 23 samples from individuals suspected of COVID-19, and six samples positive for H3N2 or respiratory syncytial virus. Two reference samples with known concentrations of SARS-CoV-2 RNA (3000 RNA copies/mL) or viral titer determined by plaque assay (105 PFU/mL) were also evaluated. The LAMP technique was employed to amplify the ORF1ab gene and the results were analyzed using a Gemini XPS fluorescence reader. Results: The RT-LAMP-CRISPR/Cas12 assay showed 100% concordance compared to RT-PCR. The RT-PCR presented a detection limit of 0.01 PFU/mL and the CRISPR/Cas12 system showed a limit of 15.6 PFU/mL. The RT-PCR sensitivity was approximately 8 RNA copies/µL and CRISPR/Cas12 at 84 RNA copies/µL. Conclusion: The RT-LAMP-CRISPR/Cas12a assay offered a promising alternative for the detection of SARS-CoV-2 and reinforces that CRISPR-based diagnostic techniques can be an alternative for fast and accurate assays.